Multifunctional performance of a carbon fiber UD lamina electrode for structural batteries. (10th November 2018) - Johannisson, Wilhelm; Ihrner, Niklas; Zenkert, Dan; Johansson, Mats; Carlstedt, David; Asp, Leif E.; Sieland, Fabian
Abstract: In electric transportation there is an inherent need to store electrical energy while maintaining a low vehicle weight. One way to decrease the weight of the structure is to use composite materials. However, the electrical energy storage in today's systems contributes to a large portion of the total weight of a vehicle. Structural batteries have been suggested as a possible route to reduce this weight. A structural battery is a material that carries mechanical loads and simultaneously stores electrical energy and can be realized using carbon fibers both as a primary load carrying material and as an active battery electrode. However, as yet, no proof of a system-wide improvement by using such structural batteries has been demonstrated. In this study we make a structural battery composite lamina from carbon fibers with a structural battery electrolyte matrix, and we show that this material provides system weight benefits. The results show that it is possible to make weight reductions in electric vehicles by using structural batteries.